Isorhamnetin Inhibits Human Gallbladder Cancer Cell Proliferation and Metastasis via PI3K/AKT Signaling Pathway Inactivation - Tianyu Zhai; Tianyu Zhai; Tianyu Zhai; Xiaoyu Zhang; Zhenyu Hei; Longyang Jin; Chao Han; Audrey Tsznam Ko; Xiaofeng Yu; Jiandong Wang; Jiandong Wang; Jiandong Wang (Frontiers Media S.A., 2021)
Gallbladder cancer (GBC) is the most common biliary tract tumor with a poor prognosis. Isorhamnetin is a flavonoid compound extracted from Hippophae rhamnoides L. and has several pharmacological effects including anti-inflammatory and anti-cancer properties. We treated GBC-SD and NOZ of GBC cell lines with different isorhamnetin concentrations in vitro. A cell counting kit-8 (CCK-8) assay, transwell assay, Hoechst 33342 stain assay, flow cytometric analysis, and a colony-forming assay were performed to investigate the effect of isorhamnetin on the proliferation, apoptosis, metastasis, and cycle arrest of GBC cells. A western blotting assay was conducted to explore the related protein expression level of GBC cells. A mice xenograft model and immunohistochemistry staining were employed to assess the effect of isorhamnetin in vivo. Isorhamnetin was found to suppress cell proliferation and metastasis, and trigger apoptosis and arrest the G2/M phase in GBC cells via the inactivation of the PI3K/AKT signaling cascade. Our findings are of clinical significance in providing a novel treatment approach for GBC.